Examination of the Use of Computer Aided Word Teaching Material for the Education of Students with Hearing Impairment - Keser, Hacer; Ozdemir, Oguzhan (Ankara Univ, Fac Educational Sciences, 2018)
In this study, it was aimed to develop and apply a vocabulary teaching material based on Mayer's Cognitive Theory of Multimedia Learning for the students with hearing impairment and to examine the effect of the material on the students via the observations of the teachers. In addition to this, considering the opinions of the teachers, the problems experienced in the schools for the students with hearing impairment and the solutions for these problems are presented. The study was conducted with 27 students in the Secondary School for Students with Hearing Impairment in Eastern Anatolia and 14 teachers in the school. In the study, phenomenology method which is one of qualitative research methods was used. The developed vocabulary teaching material was presented to students in the classrooms via intelligent boards and under the supervision of the teachers for eight weeks as an hour per week. When the findings were evaluated, it was observed that the vocabulary teaching material developed increased the vocabulary of the students and participation in the lessons, facilitated reading comprehension and to access information and the application yielded positive results. Also, at the end of the study, the study suggests the use of visually enriched and interactive materials that will be prepared by using information technology to solve the learning difficulties experienced by the students with hearing impairment.
Keywords: Information technologies; education; hearing impairment; vocabulary; instructional material; cognitive theory of multimedia